Effect of extraction conditions on obtaining pectin from agroindustrial coffee by-products - Pérez Mora, Walter Hernando; Mojica Gómez, Jaquelin (Scientia et Technica, 2023)
To present a proposal to reduce the waste generated in coffee agroindustrial production and explore potential applications of by-products, this study presents the effects of different physical factors (pH, temperature, and reflux time) on the extraction of pectin from coffee husks Coffea arabica, discarded in coffee farms of San Juan de Rioseco area after the desiccation process. The extraction is carried out by hydrolysis in an acidic medium using hydrochloric acid, precipitation by coagulation with 96% ethanol, filtration, and subsequent drying at 45 °C. Finally, the quality of the pectin obtained is evaluated by infrared spectrophotometry to determine the degree of esterification as well as the yield of the extractions carried out under different conditions. High methoxyl pectins, between 56% and 75% of esterification and yields that do not exceed 1% are obtained from wet material. An inverse temperature-degree of the esterification relationship and a direct time-yield relationship was found, according to an analysis of the main components and surface graphs, finding that the best extraction conditions are pH 2.0, temperature 90 ° C after 1 hour. The results suggest that byproducts from the coffee agro-industrial process are a promising source of pectin.